The mediating role of academic engagement in the relationship between self- regulation and self-efficacy with academic performance - Khadije Amirian, Seyede; Amani, Shirin; Saeed Abdkhodaee, Mohammad (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: The purpose of the present study was to investigate the relationship between self-regulation, self-efficacy, and academic performance with the intervention of academic engagement.Methodology: The population of the study consisted of all students at Ferdowsi University of Mashhad in the educational year of 2019-2020. The sample was composed of 367 (141 male, 226 female) students. The sampling procedure was done based on multi-level sampling. The questionnaires contained items on academic engagement, academic self-efficacyand self-regulation questionnaires as well as some basic socio-demographics. In addition, descriptive statistics, correlation, and path analysis were used in the assessment of the direct and mediating effects.Results: The results of path analysis indicated that the first observed model did not show good fit indexes. However, the revised model in which some modifications were made, such as removing the path from academic engagement to academic performance, indicated great fit indexes. Based on the revised model, academic engagement completely mediated the relationship between self-efficacy and self-regulation. Moreover, academic engagement and self-regulation partially mediated the relationship between self-efficacy and academic performance. The indirect path from academic engagement to academic achievement mediated by self-regulation was also statistically significant. Self-regulation completely mediates the relationship between academic engagement and academic performance.